Assessing Village Development Institutions' Role in Responsible Tourism: A Case Study of Rewarangga, Indonesia - Eka Kadharpa Utama Dewayani (Yayasan Ghalih Pelopor Pendidikan, 2024)
This study explores the pivotal role of Village Development Institutions (VDIs) in fostering responsible tourism in Rewarangga, Indonesia. Using a case study approach, the research examines the socio-economic and human resource contributions of VDIs to sustainable tourism practices. The findings highlight VDIs’ efforts in promoting community participation, economic diversification, and the preservation of local culture within the tourism sector. The study also identifies the challenges faced by VDIs, such as resource limitations and competing interests, that hinder their ability to fully implement responsible tourism initiatives. These insights contribute to the broader understanding of sustainable tourism development, offering practical implications for policymakers, local communities, and stakeholders in the tourism industry. By showcasing the collaborative potential of VDIs, this research underscores their vital role in advancing responsible tourism and empowering local communities in rural tourism destinations.